Transition metal atom doped C2N as catalyst for the oxygen reduction reaction: A density functional theory study. (16th October 2020) - Lin, Shangyu; Qiao, Qingan; Chen, Xin; Hu, Rui; Lai, Nanjun
Abstract: The catalytic mechanism and activity of transition metal atom doped C2 N (M-C2 N, M = Fe, Co, Ni, and Cu) for the oxygen reduction reaction (ORR) are investigated in detail by density functional theory method. All the screened M-C2 N are thermodynamically stable based on the binding energy calculations. The adsorption energy results indicate that the adsorption strength of O2 and ORR intermediates are decreased in the order of Fe-C2 N ˃ Co-C2 N ˃ Ni-C2 N ˃ Cu-C2 N, in which the adsorption energy values on Cu-C2 N are most close to those on the Pt(111). Based on the relative energy diagram of ORR, the energetically favorable pathway on Fe-C2 N and Co-C2 N is direct 4e − mechanism, in which the O–O bond is directly dissociated after the second electron transfer. While for Ni-C2 N and Cu-C2 N, the most favorable pathway is indirect 4e − mechanism, in which the H2 O2 is formed as the intermediate product. For all studied M-C2 N, the Ni-C2 N and Cu-C2 N hold better catalytic activity, which could attribute to the contribution of metal atom and part of its activated nitrogen atoms. Graphical abstract: Cu-C2 N is an effective oxygen reduction reaction (ORR) catalyst. The energetically favorable pathway of ORR on its surface is indirect 4e − mechanism. Image 1 Highlights: The ORR on transition metal atom doped C2 N is studied by DFT. The most favorable pathway on the Ni-C2 N and Cu-C2 N is indirect 4e − process. For all M-C2 N, the Ni-C2 N and Cu-C2 N hold better catalytic activity.